Sustainable Coloration of Cotton Fabrics Using Extracted Dye from Onion (Allium cepa) Peel - Abedalwafa, Mohammed Awad; Eltahir, Hafiz Ahmed (Gezira Journal of Engineering and Applied Sciences; Vol 19 No 2 (2024), 2026)
The textile industry heavily relies on synthetic dyes, making it a major source of environmental pollution. In response, this study explored the potential of onion (Allium cepa) peel extract, an agricultural waste product, as a natural dye for cotton fabrics. The objectives were to optimize dye extraction, examine how different mordants (alum, copper sulfate, and citric acid) affect color characteristics, and assess color fastness. Cotton fabrics were pre-mordanted using alum (10% owf), copper sulfate (5% owf), or citric acid (8% owf) at 70°C for 45 minutes (material-to-liquor ratio 1:20), then dyed using an aqueous extract of dried onion peels prepared at 90°C for 60 minutes (1:10 ratio), followed by dyeing at 80°C for 60 minutes with 5 g/L NaCl as electrolyte. Depending on the mordant, the dyed samples displayed hues ranging from orange-yellow to brown. Quantitative color strength (K/S) analysis revealed that copper sulfate produced the highest K/S value (2.0989), followed by alum (1.4787) and citric acid (0.9252), all significantly exceeding the unmordanted control (0.5727). A one-way ANOVA confirmed statistically significant differences among treatments (F (3,8) =47.23, p<0.001). The colorfastness to washing, light, and rubbing was highest for copper sulfate-mordanted fabrics (rating 5 for all tests), while alum yielded ratings of 4–5. Consequently, copper sulfate produced the deepest shades and best fastness, whereas alum gave brighter orange-yellow tones. Overall, onion peel extract is a viable, eco-friendly dye for cotton, offering good to excellent fastness and promoting the valorization of agricultural waste